Strain-Dependence of the Structure and Ferroic Properties of Epitaxial NiTiO3 Thin Films Grown on Different Substrates - Tamas Varga; Timothy C. Droubay; Mark E. Bowden; Libor Kovarik; Dehong Hu; Scott A. Chambers (Advances in Condensed Matter Physics)
Polarization-induced weak ferromagnetism has been predicted a few years back in perovskite MTiO3 (M = Fe, Mn, and Ni). We set out to stabilize this metastable perovskite structure by growing NiTiO3 epitaxially on different substrates and to investigate the dependence of polar and magnetic properties on strain. Epitaxial NiTiO3 films were deposited on Al2O3, Fe2O3, and LiNbO3 substrates by pulsed laser deposition and characterized using several techniques. The effect of substrate choice on lattice strain, film structure, and physical properties was investigated. Our structural data from X-ray diffraction and electron microscopy shows that substrate-induced strain has a marked effect on the structure and crystalline quality of the films. Physical property measurements reveal a dependence of the weak ferromagnetism and lattice polarization on strain and highlight our ability to control the ferroic properties in NiTiO3 thin films by the choice of substrate. Our results are also consistent with the theoretical prediction that the ferromagnetism in acentric NiTiO3 is polarization induced. From the substrates studied here, the perovskite substrate LiNbO3 proved to be the most promising one for strong multiferroism.